Virtual Facilitation Techniques for Work Teams and Communities of Prac tice. A guide for designing and running dynamic and engaging remote se ssions and meetings - AKF (2023)
This free guide aims to build the skills and confidence of people desi gning and facilitating virtual meetings, including online community of practice sessions. By the time they have gone through this guide, com munity of practice facilitators will be able to: Design an engaging an d participatory virtual session, Develop an effective, varied and real istic agenda for a virtual session, Apply a wide range of virtual faci litation techniques, and Using technology to facilitate virtual sessio ns. This toolkit was developed by the Aga Khan Foundation.